Pengaruh Perceived Usefulness, Perceived Ease Of Use, Perceived Security, Perceived Self Efficacy, Dan Trust Terhadap Minat Penggunaan Aplikasi Dana (Studi Kasus Pada Generasi Z Kota Malang) - Nurhayati, Susi Alistina; Arifin, Rois; Bastomi, Mohamad (UNIVERSITAS ISLAM MALANG, 2024)
Abstract The aim of this research is to analyze the influence of perceived usefulness, perceived ease of use, perceived security, perceived self efficacy, and trust simultaneously and partially on interest in using the Dana application. The population in the research is generation Z in Malang City, the exact number of which is unknown. The approach method uses a non-probability sampling technique, namely purposive sampling, which is a sample collection technique based on certain criteria using a questionnaire distributed to 115 respondents and using the SPSS analysis tool. The research results show that simultaneously and partially perceived usefulness, perceived ease of use, perceived security, perceived self efficacy, and trust have a significant effect on interest in using the Generation Z Fund application in Malang City. Keywords: Perceived Usefulness, Perceived Ease Of Use, Perceived Security, Perceived Self Efficacy, Trust, Interest In Use